NITROGEN REMOVAL BYAN ACTIVATED SLUDGE PROCESS WITH CROSS-FLOW FILTRATION [Perombakan Nitrogen Menggunakan Proses Lumpur Aktif yang Dilengkapi dengan Filtrasi] - Dwi Agustiyani; Takao Yamagishi (Research Center for Biology-Indonesian Institute of Sciences, 2010)
The simultaneous nitrification and denitrification in a single reactor using an activated sludge with cross-flow filtration was investigated.The reactor was a Sequencing Batch Reactor (SBR), operated on three phase conditions, phase I was continuous aeration, phase II was intermittent aeration and phase III was intermittent aeration with methanol addition. The microbial properties on the nitrogen removal processes were monitored by measuring the ammonia decreasing and nitrate production rate.The denitrification rate was also calculated from N20 gas production by acetylene inhibition method.The experiment results show that the nitrification was occurred during the aeration condition, both in the phase I and II. The denitrification was occurred in the anoxic stage (phase III).The nitrate decreasing rate in the anoxic stage (phase IIIA) increased gradually reach the value of 0.19 th mg-N/1/min. on the 8 day operation. The nitrate decreasing rate increased to be 0.45 mg/l/min in the phase IIIB and reach up to 0.70 mg/l/min in the phase IIIC in which the methanol concentrations was increased from 762 mg/L to 1016 mg/L in the phase IIIB and phase IIIC, respectively. The increasing activity of denitrification resulted in decreasing the concentration of TOC in the reactor. More than 80% nitrogen removal occurred in phase III and TOC removal efficiency in phase III reach more than 90%.